The relationship among athlete leadership behaviors and cohesion in team sports - Vincer, D. J. E.; Loughead, T. M. (The Sport Psychologist, 2010)
This study examined the influence of athlete leadership behaviors on perceptions of team cohesion. The participants were 312 athletes from 25 varsity and club level teams. Each participant completed the Group Environment Questionnaire (Carron, Widmeyer, & Brawley, 1985) that assessed cohesion and the Leadership Scale for Sports (Chelladurai & Saleh, 1980) that assessed athlete leadership behaviors. Overall, it was found that individual perceptions of Training and Instruction, and Social Support positively influenced all four dimensions of cohesion (ATG-T, ATG-S, GI-T, GI-S). Furthermore, Autocratic Behavior was negatively associated with the four dimensions of cohesion. Finally, Democratic Behavior was positively related to ATG-T. These findings provide researchers, sport psychology consultants, athletes, and coaches with some initial evidence that it is important to foster the development of athlete leader behaviors to influence the team environment.